Artificial Intelligence In Clinical Settings: Improving the practice of medicine and surgery - Khalil Ahmed Shaikh, Muhammad Kashif Shaikh, Imran Karim, Syed Zulfiquar Ali Shah, Syed Jahanghir, Muskan Kumari Bansari, (Pakistan Journal of Medical & Health Sciences, 2024)
A lot of people use the term medical technology refer to a wide range of resources that can help doctors give patients and society an improved standard of life by finding problems earlier, preventing complications, simplifying treatments, making them more effective, and cutting down on the length of hospital stays.1 In the past, medical technologies were mostly standard medical devices like implants, prosthetics and stents2. But cell phones, wearable tech, detection devices, and technology for communication have wholly transformed medical by letting clinicians carry around minimal tools driven by artificial intelligence (AI), such as apps. AI has changed the way medical technology works, and most people think of it as the part of the computer science field that can solve hard problems and find many uses in areas with lots of data but only a little theory3.